Clitoral preputial edema can be mistaken for clitoromegaly: a clinical analysis of ten cases - Mitani-Konno, Marie; Saito, Reiko; Narumi-Wakayama, Hiroko; Sakai, Yuki; Suzuki, Shuichi; Satoh, Hiroyuki; Hasegawa, Yukihiro (Frontiers in Endocrinology, 2023)
We herein reported ten, female neonates with transient clitoral preputial edema, which was mistaken for clitoromegaly. Although it is well known that the clitoris is prominent in premature, female neonates, there are as of yet no reports of clitoral preputial edema in full-term neonates.The present study was conducted to clarify the clinical course of clitoral preputial edema.Seventeen, Japanese patients aged < 6 months with suspected clitoromegaly were enrolled, and their clinical course was analyzed retrospectively. Clitoral preputial edema was defined by 1) a normal clitoral glans despite edema; and 2) the absence of established differences of sexual development with 46,XX, such as 21-hydroxylase deficiency.Ten of the 17 patients with suspected clitoromegaly had clitoral preputial edema; eight of the ten patients were full-term, and the remaining two were preterm neonates. The median age at the first visit was 8 days. Edema of the labia minora and labia majora, rugosity of the labia majora, and hymenal polyps often accompanied the clitoral preputial edema. Seven patients were examined at our division during the neonatal period, and three patients were examined in the post-neonatal period. Age at reduction of the clitoral width to < 7 mm ranged from 8 to 74 days in four of the seven neonatal patients. In the three post-neonatal patients, age to reduction in the clitoral width ranged from 107 to 243 days.Transient clitoral preputial edema is often mistaken for clitoromegaly. The key to diagnosing clitoral preputial edema lies in its characteristic appearance and improvement course.